ANALISIS KEUNTUNGAN DAN DAYA SAING KOMPETITIF USAHATANI JAGUNG HIBRIDA PIONER DAN BERSARI BEBAS DI KAWASAN USAHA AGRIBISNIS TERPADU (KUAT) SANGGAU LEDO KOMPLEK - Hendrawanto, Frangky; Yudiono, Sugeng; Aritonang, Marisi (Jurnal Sains Mahasiswa Pertanian, 2012)
Corn is one of the commodities that has a great potential to the economy of Sanggau Ledo district. Issues discussed in the study are 1) what is the average profit of farmers who use pioneered hybrid varieties and freely pollinated varieties (composite). 2) whether the varieties of pioneered hybrids are able to compete against freely pollinated varieties (composite). The purposes of this study are 1) to determine the profit levels of farming hybrid varieties of maize pioneer and freely pollinated varieties. The method used in this study was a survey. Data were collected through direct interviews with the respondents (farmers), and recording of documents from the government or related agencies. The research was deliberately located in Lembang village on the consideration that the village is one of the central areas of Jangang production in sub Sanggau Ledo district. The technique applied in this research was random sample, i.e. with population of 479 farmers, namely 177 pioneer farmers and 302 composite farmers which were taken 60 composite maize farmers. The results showed that the average profit of farming maize of pioneered hybrid varieties is Rp 6,059,000/acre/Mt); and in terms of productivity, the varieties of pioneered hybrid maize have competitiveness against composite maize varieties; Moreover, in terms of price, the varieties of pioneered hybrid maize have reasonable competitiveness against composite maize varieties. Thus, it can be concluded that the varieties of pioneered hybrid maize are competitive against the freely pollinated varieties (composite). keywords: jagung hibrida terbaik, profit, competitiveness, pioneered hybrid maize and freely pollinated maize.